THE POST-PANDEMIC ECONOMIC-INTERDEPENDENCE CONUNDRUM OF CPO-BASED INDUSTRY: THE CASE OF SUSTAINABLE KOREAN FOOD AND COSMETIC INDUSTRY - Darynaufal Mulyaman; Rudi Kogoya; Mikhail Adam (Sociae Polites, 2021)
The COVID-19 pandemic worldwide is halting every economic activity—no exception for the industry that related or originated from crude palm oil (CPO). Planting, harvesting, processing, and even industries that require oil palm as the main or supporting raw material have been delayed or choked up due to this pandemic. Many health problems originate from the destruction of nature due to the excessive extraction of natural resources. This over-extraction causes alarming natural degradation. Many things, from pandemics to global warming, pose challenges due to this ancient economic pattern. Furthermore, environmental degradation gave birth directly or indirectly to COVID-19. Many scholars said the CPO planting and harvesting is affecting the natural environment badly. Hence, a new pandemic could be born out of this. Korea, as one of the rising manufacturing economies in Asia, also needs CPO for some of its industries to some extent, like food and cosmetics. Due to the growing demand for K-Pop byproducts, food and cosmetic industries in Korea need to catch up on the market even during and post the pandemic. Thus, with the growing concern of the natural environment in the post-pandemic world, then how it will impact the Korean food and cosmetic industry, which may need a lot of CPO as one of the sources or raw materials for production? In this paper, we argue that the economic interdependence of the global supply chain remains persistent despite adjustments and shifts due to the COVID-19 pandemic. This research was conducted in a descriptive qualitative manner with the economic interdependence paradigm as the main basis for presenting the arguments for this case's analysis. Keywords: CPO, Korea, Economic Interdependence, Post-Pandemic, COVID-19